Migración, mestizaje y xenofobia en México (1910-1950) - Yankelevich, Pablo (Jahrbuch für Geschichte Lateinamerikas, 2017)
In Mexico, the population of foreigners occupies a marginal place in the country’s demographic composition. Although Mexican governments have always acknowledged the importance of attracting immigrants, the country has one of the most restrictive immigration policies in Latin America. In order to offer a possible explanation for this paradox, this essay examines the construction of the mestizo figure as a foundation for the Mexican nation. It shows how the importance of this figure grew with the ascent of the nationalist thinking derived from the 1910 Revolution, and with the impact of migratory processes resulting from the vicinity to the United States. These issues laid the foundation for xenophobic discourses, norms, and actions that, to different degrees, imbued the relationship between Mexico and foreigners.